Calm Down Collaborative: Veteran Mental Health And Self-Regulation - Chaney, Kristin M. (My University, 2020)
Calm Down Collective evaluated three established EBPs at the Department of Veteran’s Affairs and implemented their strengths into a new program that would supplement the mental health care they currently offer clients. The goal of Calm Down Collective is to help the client learn how to process incoming sensory disruptions to effectively utilize the cognitive work that should follow and alleviate the immediate symptom. The program will use a mixed-method quasi-experimental evaluation with a nonequivalent switched replication design for the participant's portion of the study and a cross-sectional survey for staff respondents. It is hypothesized that more than 50% of participants should be able to self-identify stress or sensory disruptions. The second hypothesis is that they should be able to intervene on their own behalf with the sensory aides provided by the program at least 75% of the time by their final phone interview. Using a paired T-test, pre-test and post-test survey data will be compared to mark a progression in self-regulation as well as assess any change in symptoms using the PSSI-5 PTSD Symptom Scale Interview. The Calm Down Collective will support the dominant treatment plan by providing additional coping skills in the gaps where the client is learning how to self-regulate.